Cu(OTf)(2) catalyzed high yield synthesis of hantzsch 1,4-dihydropyridines - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2007)
Copper(II) triflate catalyzes efficiently the three-component condensation of aldehydes, beta-ketoesters and ammonium acetate in acetonitrile at 25 degrees C to afford the corresponding Hantzsch 1,4-dihydropyridines in high yields.
Keywords: 4-dihydropyridines; anti-hypertensive drug; calcium channel blockers; cardiovascular diseases; Hantzsch 1; three-component condensation